Prognostic significance of day‐by‐day in‐hospital blood pressure variability in COVID‐19 patients with hypertension. Issue 3 (7th February 2022) - He, Chunyan; Liu, Chuan; Yang, Jie; Tan, Hu; Ding, Xiaohan; Gao, Xubin; Yang, Yuanqi; Shen, Yang; Xiang, Hedong; Ke, Jingbin; Yuan, Fangzhengyuan; Chen, Renzheng; et al.
Abstract: Hypertension is the most common comorbidity in patients with coronavirus disease 2019 (COVID‐19) and increases in‐hospital mortality. Day‐by‐day blood pressure (BP) variability (BPV) is associated with clinical outcomes in hypertensive patients. However, little information is available on the association of BPV with the outcomes of COVID‐19 patients with hypertension. This study aimed to demonstrate whether day‐by‐day in‐hospital BPV had prognostic significance in these patients. The authors included 702 COVID‐19 patients with hypertension from Huoshenshan Hospital (Wuhan, China), who underwent valid in‐hospital BP measurements on at least seven consecutive days. Day‐by‐day BPV was assessed by standard deviation (SD), coefficient of variation (CV), and variation independent of mean (VIM). Overall, patients with severe COVID‐19 and non‐survivors had higher BPV than moderate cases and survivors, respectively. Additionally, higher BPV was correlated with greater age and higher levels of C‐reactive protein, procalcitonin, high‐sensitive cardiac troponin I, and B‐type natriuretic peptide. In multivariable Cox regression, SD of systolic BP (SBP) was predictive of mortality [hazard ratio (HR) 1.17, 95% confidence interval (CI) 1.05–1.30] as well as acute respiratory distress syndrome (ARDS) (HR 1.09, 95% CI 1.01–1.16). Similar trends were observed for CV and VIM of SBP, but not indices of diastolic BP variability. The authors demonstrated that day‐by‐day in‐hospital SBP variability can independently predict mortality and ARDS in COVID‐19 patients with hypertension. And high BPV might be correlated with severe inflammation and myocardial injury. Further studies are needed to clarify whether early reduction of BPV will improve the prognosis of these patients.